Dendronized fluorosurfactant for highly stable water-in-fluorinated oil emulsions with minimal inter-droplet transfer of small molecules - Mohammad Suman Chowdhury (Nature Portfolio, 2019)
Microdroplets are used as chemical and biological reactors; however, stability and inter-droplet transfer are major issues. Here, the authors report on the development of dendritic glycerol-based surfactants for the creation of stable microdroplets and demonstrate application for PCR, minimal emulsion, and cell encapsulation.